Information literacy effect on religious moderation among students of islamic and public universities - Hak, Ade Abdul; Putra, Riyan Adi (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: Understanding how differences in institutional background and information literacy influence students’ attitudes and practices toward religious moderation in media is essential. Purpose: To examine the comparison of religious moderation among Library Science students in Islamic religious universities (PTKI) and public universities (PTU) in Indonesia, focusing on the role of information literacy. Method: A quantitative approach was used, involving 94 students from four universities recruited through an online survey. The data collected were analyzed using Jamovi. Findings: There is a positive relationship between information literacy and religious moderation, with higher information literacy associated with greater religious moderation. The impact of Information Literacy is more significant in PTKI, as seen from the steeper slope of the regression line. This could indicate that, in PTKI, information literacy plays a significant role in shaping religious moderation. PTU students exhibit higher levels of religious moderation at lower levels of information literacy, which could be due to other factors, such as educational background or social environment. Conclusion: Different approaches may be needed for PTKI and PTU to improve religious moderation through information literacy. Further research is required to understand other factors that influence this relationship, such as curriculum, student mindset, or sources of information accessed.